2021
DOI: 10.21123/bsj.2021.18.3.0486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt and Osmotic Stresses on the Activity of Some Antioxidant Enzymes and Biochemical Traits in Catharanthus roseus

Abstract: The experiment has been carried out in the Syrian National Commission of Biotechnology, during the growing season 2018/2019, to study the effect of abiotic stresses (salinity and osmotic stresses) on the activity of some antioxidant enzymes and biochemical traits in Catharanthus roseus. The experiment has been laid according to (CRD) with three replications. The seeds have been sterilized by NaOCl solution (0.5% v/v), then planted on MS medium. Plantlets have been moved to MS medium enriched with NAA (1 mg.L-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Hadi [35] investigated that increasing mannitol concentration led to an increase in the accumulation of proline, and another study using PEG to induce stress found an increase in proline content [36].…”
Section: Effect Of Gamma Ray and Mannitol Stress On Ascorbic Acid (Vi...mentioning
confidence: 99%
“…Hadi [35] investigated that increasing mannitol concentration led to an increase in the accumulation of proline, and another study using PEG to induce stress found an increase in proline content [36].…”
Section: Effect Of Gamma Ray and Mannitol Stress On Ascorbic Acid (Vi...mentioning
confidence: 99%
“…The boxes were incubated at 24 ± 2°C, 16 hours of light, and 8 hours of darkness alternately until the seed germinated. After 45 days, they were replanted on MS medium supplemented with two hormones, 6-benzyl adenine (BA) (2 mg L -1 ) and Naphthalene Acetic Acid (NAA) (1 mg L -1 ) (from MERCK) [23], to obtain sufficient plant material needed to carry out the callus development experiments.…”
Section: Seeds Germinationmentioning
confidence: 99%